Water retention mechanism of cellulose ethers in calcium sulfoaluminate cement-based materials - Wan, Qin; Wang, Zhaojia; Huang, Tianyong; Wang, Ru (Construction & building materials, 2021)
•HEMC show better water retention capability in CSA cement mortar than HEC.•HEMC and HEC below 0.1% dosage in CSA cement system achieve water retention through its water sorption effect.•HEC exceed 0.1% dosage in CSA cement system achieve water retention by its adsorption on cement.•HEMC exceed 0.1% dosage in CSA cement system achieve water retention by forming polymer network. To explore the mechanism to water retention of cellulose ether (CE) in calcium sulfoaluminate (CSA) cement-based materials, three cellulose ethers (CEs) with similar viscosity but different substitution groups were selected in this paper, namely hydroxyethyl cellulose (HEC) and hydroxyethyl methyl cellulose (HEMC) with high and low degree of substitution (DS). Water retention of CE modified CSA cement mortar with different CE dosages was characterized by filter paper method. The water state and content in CE modified CSA cement paste were determined by low field nuclear magnetic resonance (1H NMR). The adsorption and dispersion characteristics of CE in CSA cement paste were analyzed by measuring the organic carbon content in the pore solution. Combined with the measurement of dynamic viscosity and surface tension of pore solution, the mechanism to water retention of CEs in CSA cement-based materials was comprehensively analyzed. The results show that the addition of CE can significantly improve the water retention of CSA cement mortar. At the same dosage, the water retention effect of HEMC is better than HEC, and DS has little effect on the water retention capacity of HEMC. The mechanism to water retention of HEC and HEMC added less than 0.1% dosage in system is governed by water sorption effect of CE. While more than 0.1% dosage, HEC and HEMC in CSA cement-based materials achieve water retention respectively through the adsorption of CE on cement and the formation of three-dimensional polymer network in pore solution.